2017
DOI: 10.1016/j.ydbio.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Patterning and morphogenesis of the intricate but stereotyped oikoplastic epidermis of the appendicularian, Oikopleura dioica

Abstract: Mechanisms for morphogenetic processes that generate complex patterns in a reproducible manner remain elusive. Live imaging provides a powerful tool to record cell behaviors. The appendicularian, Oikopleura dioica, is a planktonic tunicate that has a rapid developmental speed, small number of cells (less than 3500 cells in a juvenile), and a transparent body. The trunk epidermis, called the oikoplastic epithelium (OE), has elaborate cellular arrangements showing a complex pattern to secrete so-called "house" m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Recently, Kishi et al (2017) These proteins seem to be specific to appendicularians, because in a comparison between the genomes of Oikopleura dioica and Ciona robusta (then still called C. intestinalis, but see Brunetti et al, 2015, Hosp et al (2012) could not identify homologous genes in the C. robusta genome. However, the authors showed that Linking this molecular level knowledge to higher structural levels has been attempted, yet little can be stated in this respect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Kishi et al (2017) These proteins seem to be specific to appendicularians, because in a comparison between the genomes of Oikopleura dioica and Ciona robusta (then still called C. intestinalis, but see Brunetti et al, 2015, Hosp et al (2012) could not identify homologous genes in the C. robusta genome. However, the authors showed that Linking this molecular level knowledge to higher structural levels has been attempted, yet little can be stated in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kishi et al (2017) have investigated the ontogenetic pattern of cell divisions and movement that leads to the stereotypic arrangement of oikoplastic cells and presented a clear nomenclature for the individually recognizable cells based on the positions of nuclei that we adopt in the present study. In a pioneering study, Thompson et al (2001) characterized specific expression domains of individual combinations of genes in the different oikoplastic fields among them the diverse and numerous oikosins, coding for the respective proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we determined the genome sequence of Japanese O. dioica. Using the same population, we have developed tools for molecular, cellular, and genetic techniques, including gene knockdown methods (Omotezako et al, 2013(Omotezako et al, , 2015(Omotezako et al, , 2017, fluorescent live imaging of larvae (Kishi et al, 2014(Kishi et al, , 2017, and maternal and zygotic transcriptomes of the eggs and larvae (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These have been used to gain insights into cell migration (Kishi et al, 2014), patterning of epidermal cells (Kishi et al, 2017), left-right patterning (Onuma et al, 2020) and meiotic arrest of the unfertilized egg (Matsuo et al, 2020). Moreover, transcriptome-wide comparison has implied a high level of sequence variation between the Japanese and Norwegian O. dioica (Wang et al, 2015): only 91.0% and 94.8% of exon sequences were conserved at nucleotide and amino acid levels on average, respectively.…”
Section: Introductionmentioning
confidence: 99%